2019
DOI: 10.4274/cayd.galenos.2019.47568
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin B12 Deficiency in Infants Cause Severe Clinical Symptoms Necessitating Intensive Care?

Abstract: Introduction: Cobalamin (Cbl) deficient infants are mostly outpatients. Medical literature is very limited concerning infants with severe Cbl deficiency requiring intensive care. The aim of this study was to describe infants requiring intensive care whose health issues were primarily related to Cbl deficiency. Methods: This is a single-center retrospective observational study performed at the pediatric intensive care unit at a children's hospital. Patients aged 6-24 months with low serum Cbl level coexisting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We know better the relationship of Cbl deficiency and diseases. [1][2][3]8 Ideas are being developed about how vitamin B12 deficiency changes the clinics of other diseases. Autoanalysers offer fast, inexpensive, and results available on the same day and then we can use these results to decide patient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We know better the relationship of Cbl deficiency and diseases. [1][2][3]8 Ideas are being developed about how vitamin B12 deficiency changes the clinics of other diseases. Autoanalysers offer fast, inexpensive, and results available on the same day and then we can use these results to decide patient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B12 deficiency is more common in developing countries. The prevalence varies between 3-40% in children in the world [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The admission complaints of individuals with Vitamin B12 deficiency vary among age groups. Patients may be asymptomatic or may be diagnosed with significant life-threatening hematological and neurological diseases [4][5][6]9]. Copy@ Erhan Aygün neurological symptoms, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although Cbl deficiency is frequently discussed in the literature, the number of publications is very limited concerning children with high Cbl levels. However, some studies have recently reported that elevated serum levels of Cbl might be a sign of serious and life-threatening diseases, such as myeloproliferative disease, acute hepatitis, severe alcoholic liver disease, and cirrhosis [ 4 , 7 9 ].…”
Section: Highlight Key Pointsmentioning
confidence: 99%